Pemberdayaan Komunitas SEPATAH KATA Berbasis Pemanfaatan Limbah Pelepah Pisang Melalui Pelatihan Kerajinan Tangan - Sulaeman Fityan Saputra; Dwi Rahma Atiqilah Rizki; Abdul Malik; Yudi Siswanto (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Banana stem waste is one of the agricultural wastes commonly found in rural areas, but it has not been optimally utilized by the community. Most banana leaves are still considered as agricultural waste with no economic value. This Community Service activity aims to empower the SEPATAH KATA Community through handicraft training based on the utilization of banana stem waste in order to improve the community's skills, environmental awareness, and economic independence. The activity was carried out using an educational approach to increase knowledge, a persuasive approach to foster motivation and environmental awareness, and a participatory approach through hands-on practice, with reference to the principles of Participatory Action Research. The results of the activity showed an increase in participants' understanding and skills in processing banana stem waste into handicraft products, particularly bags. Additionally, participants began to realize that banana stem waste has economic value and potential to be developed as a business. This activity contributed to strengthening community capacity and encouraging the sustainable use of local resources to meet needs.